Advances in the study of miRNAs in chronic kidney disease with cardiovascular complications - Zou, Chenchen (Frontiers in Physiology, 2023)
Chronic kidney disease (CKD) is characterised by gradual loss of renal function and cardiovascular disease (CVD) as its principal consequence. CVD is a substantial source of morbidity and death in the CKD population and a growing global concern. Because there are no reliable early biomarkers to follow the progression of CKD and predict the risk of complications, research into such molecules continues. Many studies have demonstrated that miRNAs are potentially important variables in CKD, are very stable in blood, and may be employed as diagnostic and prognostic markers for various disorders. Vascular calcification (VC) is a cell-mediated process that necessitates genetic defects in the combined cardiovascular issues of CKD and may be modulated in part by miRNAs. Numerous miRNAs have been linked to the progression of vascular calcification. Many miRNAs have been discovered as being important in ventricular hypertrophy, including miRNA-30, miRNA-212, and miRNA-133. Endothelium miR-126, miR-92a-3p, and others are important regulators of angiogenesis, endothelium repair, and homeostasis. Several interesting non-invasive miRNA biomarkers in CKD/CVD have been found, with the potential to enhance diagnostic accuracy, predict prognosis, track disease progression, and serve as novel therapy targets. However, large-scale clinical studies are still needed to determine the therapeutic utility of miRNA.